Cardiovascular Hypertension-Mediated Organ Damage in Hypertensive Urgencies and Hypertensive Outpatients - Vallelonga, Fabrizio; Cesareo, Marco; Menon, Leonardo; Airale, Lorenzo; Leone, Dario; Astarita, Anna; Mingrone, Giulia; Tizzani, Maria; Lupia, Enrico; Veglio, Franco; Milan, Alberto (Frontiers in Cardiovascular Medicine, 2022)
Background: Prevalence of hypertension mediated organ damage (HMOD) in patients attending the Emergency Department (ED) with symptomatic blood pressure (BP) rise is unknown, and whether HMOD varies between asymptomatic and symptomatic grade III hypertension patients is unclear. Aim: To investigate cardiac and vascular HMOD in hypertensive urgencies (HU) and in asymptomatic outpatients with grade 1–2–3 hypertension. Methods: Patients attending the EDwith a symptomatic blood pressure (BP) rise 180/110 mmHg were prospectively enrolled (HU group), after exclusion of acute organ damage. HMOD and BP were assessed after 72h from ED discharge in office setting. These patients were matched by age and sex to outpatients with grade 3 hypertension (Grade 3 group), and by age, sex, and 72h office BP values to outpatients with any grade hypertension (Control group). Results: 304 patients were enrolled (76 HU group, 76 Grade 3 group, 152 Control group). Grade 3 patients had increased left ventricular mass (LVMi) compared to HU patients (106.9±31.5 vs. 96.1±30.7 g/m2, p=0.035). Severe left ventricular hypertrophy (LVH) was more frequent in Grade 3 (21.1% vs 5.3% p=0.004); pulse wave velocity (PWV) was similar in the two groups. There was no difference in LVMi between ED and Control patients (96.1±30.7 vs. 95.2±26.6 g/m2, p=0.807). LVH prevalence was similar (43.4% vs. 35.5%, p=0.209, respectively), but HU patients had thicker interventricular septum (11.9±2.2 vs. 11.1±2.2 mm, p=0.007). PWV was similar between these two groups. HU patients needed more antihypertensive drugs than Control patients (2 vs. 1, p<0.001). Conclusions: HU patients had better cardiac HMOD profile than outpatients with grade 3 hypertension. Their cardiac and vascular HMOD is more comparable to outpatient with similar in-office BP, although they need more antihypertensive medications.